2016
DOI: 10.4111/icu.2016.57.s1.s89
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and urothelial carcinoma of the bladder: A review

Abstract: The incidence of urothelial carcinoma of the urinary bladder (bladder cancer) remains high. While other solid organ malignancies have seen significant improvement in morbidity and mortality, there has been little change in bladder cancer mortality in the past few decades. The mortality is mainly driven by muscle invasive bladder cancer, but the cancer burden remains high even in nonmuscle invasive bladder cancer due to high recurrence rates and risk of progression. While apoptosis deregulation has long been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…It has been well-demonstrated that autophagy depends on Atg5/Atg7, which is associated with microtubule-associated protein LC3 truncation and lipidation and may originate directly from the ER membrane and other membrane organelles. ATG5 and ATG7 regulate the formation of autophagosomes, but they are separated from autophagosomes after the formation of autophagosomes 35 , 36 . Therefore, there is an upregulation in the expression of ATG5 and ATG7, but it may not be a positive correlation between the ATG5/ATG7 mRNA levels and the autophagosomes in the spatial-temporal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-demonstrated that autophagy depends on Atg5/Atg7, which is associated with microtubule-associated protein LC3 truncation and lipidation and may originate directly from the ER membrane and other membrane organelles. ATG5 and ATG7 regulate the formation of autophagosomes, but they are separated from autophagosomes after the formation of autophagosomes 35 , 36 . Therefore, there is an upregulation in the expression of ATG5 and ATG7, but it may not be a positive correlation between the ATG5/ATG7 mRNA levels and the autophagosomes in the spatial-temporal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a constitutively active evolutionary conserved physiologic catabolic process that is maintained at a basal rate by cells throughout the body 16. Accumulating studies showed that autophagy protects some cancers against anticancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder urothelial carcinoma (BUC) is one of the most common malignant tumors of the urinary system and is characterized by rapid progression and a high rate of recurrence (1,2). BUC recurs in approximately 50% of patients after surgery, and the 5-year overall survival rate for patients who develop or present with metastatic disease is a dismal 6% (3).…”
Section: Introductionmentioning
confidence: 99%